Oil, gas, and mining a sourcebook for understanding the extractive industries - Cameron, Peter D.; Stanley, Michael C. (World Bank E-Library Archive, 2017)
This new sourcebook admirably illuminates the spectrum of integrated policy interventions necessary to transform natural resource wealth into sustainable development, ranging from the allocation of resource extraction rights to the use and distribution of revenues. It recognizes and emphasizes the importance of the political and institutional context. The sourcebook ably breaks down the implications of the type of natural resource, describes the organization of the industry, and provides illustrative examples and useful citations from the literature. How individual governments, companies, and the world as a whole approach the management and governance of mineral and energy resources will be important in determining the success or failure of the sustainable development goals (SDGs). Given the breadth of the SDGs and the targets therein, as well as the myriad challenges of natural resource governance, the new sourcebook and the community of researchers and practitioners that continues to grow around it will help to shed light on the path ahead